Foresight as a mechanism for inclusion? Comparative analysis of gender and social inclusion within the CCAFS scenario-based policy formulation processes - Marty, Edwige (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Starting from 2010, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) scenarios team has led several future scenario-guided policy formulation processes under the FP1 Flagship Priorities and Policies for CSA. These scenario-based processes combined stakeholders’ workshops with quantitative modelling to guide planning for food and nutrition secure futures under changing climatic conditions. While earlier scenarios focused on the regional level, the scope have since expanded to encompass multiple regional and national policy development processes. The second phase of the scenario project also stressed the need to further integrate gender, youth issues and other social inclusion considerations within the scenario-guided processes, using “foresight as a mechanism for inclusion” (CCAFS, 2017). The following working paper takes stock of the successes and challenges in integrating gender and social inclusion considerations by reviewing 15 selected scenario-guided processes across Latin America, East and West Africa, South Asia and South-East Asia. The review combines reflective qualitative interviews with the scenarios team and content analysis of key output documents for each case. The findings suggest important constraints of time, format, dedicated funding, and human resources but the use of scenarios was found to help level the playing field thanks to highly participatory methods. Planning for side consultations with marginalised groups, longer engagement, and bringing in experts in gender and social inclusion were also noted to have had positive effects in several scenario-guided policy formulation processes. Significant efforts remain nonetheless necessary to ensure that gender, youth and other social inclusion dynamics are considered in a meaningful way in both process participation and policies outputs.